2019
DOI: 10.1371/journal.pone.0221709
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of neonatal versus prenatal screening for congenital toxoplasmosis

Abstract: BackgroundCongenital Toxoplasmosis (CT) can have severe consequences. France, Austria, and Slovenia have prenatal screening programs whereas some other countries are considering universal screening to reduce congenital transmission and severity of infection in children. The efficiency of such programs is debated increasingly as seroprevalence among pregnant women and incidence of congenital toxoplasmosis show a steady decrease. In addition, uncertainty remains regarding the effectiveness of pre- and postnatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 56 publications
1
24
0
2
Order By: Relevance
“…The morbidity of congenital toxoplasmosis in children is very high and true suffering may be underestimated (Havelaar et al, 2007;Bénard et al, 2008;Stillwaggon et al, 2011;Torgerson and Mastroiacovo, 2013;El Bissati et al, 2018;Binquet et al, 2019;Picone et al, 2020). One study estimated 1.2 million disability-adjusted life years and an estimated 190 100 cases globally (Torgerson and Mastroiacovo, 2013).…”
Section: Background Of Congenital Toxoplasmosismentioning
confidence: 99%
“…The morbidity of congenital toxoplasmosis in children is very high and true suffering may be underestimated (Havelaar et al, 2007;Bénard et al, 2008;Stillwaggon et al, 2011;Torgerson and Mastroiacovo, 2013;El Bissati et al, 2018;Binquet et al, 2019;Picone et al, 2020). One study estimated 1.2 million disability-adjusted life years and an estimated 190 100 cases globally (Torgerson and Mastroiacovo, 2013).…”
Section: Background Of Congenital Toxoplasmosismentioning
confidence: 99%
“…It was estimated that in 2008, based on a seroprevalence of 38%, the cost was EUR 43 million per year and that the decreasing seroprevalence was increasing the cost by EUR 1 million per year due to additional monthly testing [ 48 ]. One French study, using a seroprevalence of 36.7%, estimated an additional cost of EUR 232,631 per direct toxoplasmosis-related event avoided when comparing current prenatal screening to a potential neonatal screening scenario [ 49 ]. When a wider range of adverse events was included the cost per outcome avoided reduced to EUR 14,826.…”
Section: Discussionmentioning
confidence: 99%
“…After duplicate removals, 716 articles were considered eligible for screening by title and abstract. After full-text screening, 35 articles were included for the final assessment (see Appendix C for the PRISMA flow diagram) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. No additional studies were found on the websites of the INAHTA HTA agencies.…”
Section: Resultsmentioning
confidence: 99%